LAZY Gene Family in Plant Gravitropism - Jiao, Zhicheng; Du, Huan; Chen, Shu; Huang, Wei; Ge, Liangfa (Frontiers in Plant Science, 2021)
Adapting to the omnipresent gravitational field was a fundamental basis driving the flourishing of terrestrial plants on the Earth. Plants have evolved a remarkable capability that not only allows them to live and develop within the Earth’s gravity field, but it also enables them to use the gravity vector to guide the growth of roots and shoots, in a process known as gravitropism. Triggered by gravistimulation, plant gravitropism is a highly complex, multistep process that requires many organelles and players to function in an intricate coordinated way. Although this process has been studied for several hundred years, much remains unclear, particularly the early events that trigger the relocation of the auxin efflux carrier PIN-FORMED (PIN) proteins, which presumably leads to the asymmetrical redistribution of auxin. In the past decade, the LAZY gene family has been identified as a crucial player that ensures the proper redistribution of auxin and a normal tropic response for both roots and shoots upon gravistimulation. LAZY proteins appear to be participating in the early steps of gravity signaling, as the mutation of LAZY genes consistently leads to altered auxin redistribution in multiple plant species. The identification and characterization of the LAZY gene family have significantly advanced our understanding of plant gravitropism, and opened new frontiers of investigation into the novel molecular details of the early events of gravitropism. Here we review current knowledge of the LAZY gene family and the mechanism modulated by LAZY proteins for controlling both roots and shoots gravitropism. We also discuss the evolutionary significance and conservation of the LAZY gene family in plants.